2019
DOI: 10.1016/j.clinbiomech.2018.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baseplate positioning on fixation of reverse total shoulder arthroplasty

Abstract: Background: The glenoid component in reverse total shoulder arthroplasty is recommended to be positioned inferiorly or with a downward tilt with the intention of reducing scapular notching. However, it is still unclear whether modifying the position of the glenoid prosthesis affects implant stability. The aim of this study was to determine the association between implant positioning and glenoid prosthesis fixation using Grammont reverse total shoulder arthroplasty. Methods: Four positions for the glenoid prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…5 ASCR provides a fulcrum to the deltoid lever arm without compromising the native glenohumeral center of rotation, which allows the shoulder girdle to function in a physiological balance and prevents several unsolved mechanical problems of current reverse total shoulder arthroplasty implants that are used in the treatment of IRCTs. 2,20,40,48,52…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ASCR provides a fulcrum to the deltoid lever arm without compromising the native glenohumeral center of rotation, which allows the shoulder girdle to function in a physiological balance and prevents several unsolved mechanical problems of current reverse total shoulder arthroplasty implants that are used in the treatment of IRCTs. 2,20,40,48,52…”
Section: Discussionmentioning
confidence: 99%
“…5 ASCR provides a fulcrum to the deltoid lever arm without compromising the native glenohumeral center of rotation, which allows the shoulder girdle to function in a physiological balance and prevents several unsolved mechanical problems of current reverse total shoulder arthroplasty implants that are used in the treatment of IRCTs. 2,20,40,48,52 This is the first study to date to report the reliability statistics for the MRI outcomes of graft integrity, fatty infiltration, and atrophy of the rotator cuff muscles after ASCR. 11,12,28,29,36,37,41,50 The proportion of complete graft tears was 21.1% at 3 years, which was the most reliable MRI outcome of the present study, whereas the proportion of partial tears was less reliable and ranged from 10.5% to 21.1% across the 3 raters.…”
Section: Discussionmentioning
confidence: 99%
“…The positioning of the baseplate in line with the lower border of the glenoid bone is implicated in reducing notching, decreasing bone resorption, and consequently improving the implant durability. 36 – 38 The Exactech brand baseplate used in our study is recommended to be positioned on the lower edge of the glenoid. We found that the surgeons’ ability to correctly position the baseplate in relation to the inferior glenoid, even without intraoperative 3D technology, is excellent (Radiologist 1 and 2 measurements reported 97.1% and 95.7% respectively, and were not influenced by the GBD).…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling of RTSA facilitates estimation of muscle and joint loading, which is currently impossible to measure non-invasively in vivo. Modeling and simulation of RTSA has played a critical role in guiding implant positioning and surgical technique [19][20][21][22], prosthesis selection [23,24], implant design [25,26], and post-operative rehabilitation prescription [27,28]. To date, most modeling and simulation tools require high levels of expertise and are generally restricted to the research setting.…”
Section: Computational Modeling Techniquesmentioning
confidence: 99%